ROS-induced cytosolic release of mitochondrial PGAM5 promotes colorectal cancer progression by interacting with MST3 - Shiyang Wang; Xi Wu; Wenxin Bi; Jiuzhi Xu; Liyuan Hou; Guilin Li; Yuwei Pan; Hanfu Zhang; Mengzhen Li; Sujuan Du; Mingxin Zhang; Di Liu; et al. (Nature Communications)
Abstract Aberrant release of mitochondrial reactive oxygen species (mtROS) in response to cellular stress is well known for promoting cancer progression. However, precise molecular mechanism by which mtROS contribute to epithelial cancer progression remains only partially understood. Here, using colorectal cancer (CRC) models, we show that upon sensing excessive mtROS, phosphatase PGAM5, which normally localizes to the mitochondria, undergoes aberrant cleavage by presenilin-associated rhomboid-like protein (PARL), becoming released into the cytoplasm. Cytosolic PGAM5 then directly binds to and dephosphorylates MST3 kinase. This, in turn, prevents STK25-mediated LATS1/2 phosphorylation, leading to YAP activation and CRC progression. Importantly, depletion of MST3 reciprocally promotes accumulation of cytosolic PGAM5 by inducing mitochondrial damage. Taken together, these findings demonstrate how mtROS promotes CRC progression by activating YAP via a post-transcriptional positive feedback loop between PGAM5 and MST3, both of which can serve as potential targets for developing next-generation anti-colon cancer therapeutics.